CONDUCTA ALIMENTARIA EN TRES ESPECIES DE ACRIDIDOS CHILENOS (ORTHOPTERA: ACRIDIDAE) (Acta Entomológica Chilena, 2022)
The results of the aplication of the feeding test on three chilean acridid species: Trimerotropis ochraceipennis, Tetrixocephalus sergioi and Schistocerca americana, are presented.The data are summarized in three Tables, which show the degree of the specie’s preferences for the plants found in their habitat. A brief account of the applied techniques is offered.